Mechanical and physical properties of sawdust reinforced epoxy resin composites - Hamzah, Khairum; Ali, Farhan Afif; Khashi’ie, Najiyah Safwa; Waini, Iskandar; Mustafa, Nuzaimah; Nik Long, Nik Mohd Asri (GNU General Public License, 2022)
Sawdust is one of the beneficial by-products of wood production, along with a number of others. In the construction of structures, sawdust, considered a waste material, is successfully used to create sawdust concrete. In the present study, a new analysis of the mechanical and physical properties of sawdust-reinforced epoxy resin composites (SRER) was presented. This mixing composite was fabricated using the compression molding techniques to produce three eco-friendly ratios between natural and synthetic materials: 75% of sawdust and 25% of epoxy (75S25E), 80% of sawdust and 20% of epoxy (80S20E), and 85% of sawdust and 15% of epoxy (85S15E). The images of the sawdust material were captured using Nikon SMZ 745T microscope, and their mechanical properties were analyzed using tensile, impact, and surface roughness tests. The collected data were analyzed using statistical analysis. Numerical computations and graphical demonstrations were carried out to observe the mechanical and physical properties of the SRER composite according to the three ratios. Their mechanical and physical properties will affect the different ratios of SRER composite. The outcomes demonstrated that due to the synergistic effect of reinforcements, the composite with 80% of sawdust had better mechanical properties than the other eco-friendly ratios composites. Furthermore, the mechanically tested samples were subjected to a surface roughness test to investigate the impact of the speed parameters of the CNC router machine spindle. The results show the significance of the CNC router machine spindle speed parameters for the eco-friendly ratios of SRER composite.